DİNİ TEMELLERİ AÇISINDAN EŞİTLİK - BOSAT, SAİT (Fırat Üniveristesi, 2013)
İnsanlık tarihi boyunca çeşitli din ve milletlere mensup insanlar içerisinde ırkçılık halkçılık gibi ayrımcılığa dayalı eğilimler olagelmiştir. Bunların bazıları Yahudilik ve Hristiyanlıkta olduğu gibi dine, bazıları ise Hint ve Mecusilerde olduğu gibi yaratılışın aslına dayandırılmıştır. İslam'ın sosyo-kültürel tarihi incelendiğinde buna benzer eğilimler hemen her dönem vuku bulmuştur. Buna bağlı olarak başta Araplar olmak üzere çeşitli milletler bu savlarını desteklemek amacıyla naslar oluşturmuş ve dini, bu amaçlarına referans olarak kullanmak istemişlerdir.Anahtar Kelimeler: Eşitlik, İnsan, Asabiyet, Mevâli, Şuûbiye, İslam, Nass, Kelam

Throughout the history of humanity, there has been a tendency based on discrimination such as racism and, populism in people from various religions and nations. Some of them has been based upon religion like in Christianity and Judaism, but some of them has been based upon the fact of original creation, as well as the Indian and the Magus. When examined socio-cultural history of Islam in every period, similar tendencies have occurred nearly all the periods. Accordingly, the various nations, especially the Arabs, have made up some evidences in order to support their assertions, and they have wanted to use the religion for the sake of their aims as a reference.Key Words: Equality, Human, Irritability, Mevâli, Şuûbiye, Islam, Nass, Kalam
Foundations for religious equality
Keywords: Din